The Role of Vesicles in Transporting of Cholera Toxin - V. P. Zyuzina; O. A. Yakusheva; L. P. Alekseeva; V. V. Evdokimova; D. I. Simakova (Проблемы особо опасных инфекций, 2023)
The review reports on the secretion pathways of the main virulence factor of Vibrio cholerae, cholera toxin, both through the two-stage Sec-dependent type 2 secretion system and with the help of vesicles of the outer membrane of V. cholerae. The ways of toxin transfer into the host organism, depending on its form, are discussed. The well-studied free soluble cholera toxin is secreted extracellularly and transmitted in a GM1-dependent manner through cholesterolrich lipid rafts. The transfer of cholera toxin associated with vesicles has advantages over free toxin, because substances inside the outer membrane vesicles are protected from external proteases and host antibodies by the membrane that forms the vesicle. Vesicular transporting of cholera toxin into the target cell occurs via clathrin-dependent, caveolin-dependent and lipid raft-dependent endocytosis. The specific transport route is determined by the structure of the vesicles. Clathrindependent endocytosis is described for V. cholerae strains cultivated at low osmolarity of the medium, whose outer membrane vesicles contain the cholera toxin subunit A inside. Lipid raft-dependent endocytosis is characteristic of vesicles in which cholera toxin is located on the surface. In addition, endocytosis of V. cholerae outer membrane vesicles through structures known as caveolae is presented.